Response of soybean (Glycine max) to different sources and levels of sulphur application - DHERI, G S; SAINI, SAT PAL; BRAR, B S; SANDHU, O S (The Indian Journal of Agricultural Sciences, 2021)
Sulphur (S) is an important nutrient element for increasing soybean [Glycine max (L.) Merrill.] yield and oil content. The present study was conducted for three years to evaluate the effect of four levels of S (0, 20, 30 and 40 kg S/ha) applied through three different S sources (single super phosphate: SSP), gypsum and bentonite-S). Soybean responded to S application and its yield increased significantly up to 30 kg S/ha through different S sources. Across the S levels, the improvement in seed yield under SSP, gypsum and bentonite-S ranged from 0.257, 0.253 and 0.280 t/ha over the control. Application of sulphur has a positive effect on S concentration and total S uptake by the crop. All the three sources of S recorded equivalent effect on soybean at 30 kg S/ha. From the above, it may be concluded that application of 30 kg S/ha has maximized the productivity of soybean under sulphur deficient soils. The returns per rupee spent values increased with an increase in S application from 20 to 30 kg S/ha, indicating higher returns from these levels per unit of money spent on sulphur. Sulphur applied through SSP, gypsum and bentonite was equally efficient in meeting the S requirement of soybean under S deficient soils.